2011
DOI: 10.1038/modpathol.2011.88
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers and clinical behavior of uterine carcinosarcomas: focus on the epithelial tumor component

Abstract: Carcinosarcomas (malignant mixed Mü llerian tumors) of the uterus are rare and aggressive malignancies consisting of an epithelial (carcinoma) and a mesenchymal (sarcoma) tumor component and are considered as metaplastic endometrial carcinomas. This study evaluated molecular characteristics and clinical behavior of uterine carcinosarcomas to improve treatment regimens in the future. Immunohistochemical expression of estrogen receptor-a and -b, progesterone receptor-A and -B, MLH1, MSH2, MSH6, PTEN (phosphatase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 40 publications
4
97
1
1
Order By: Relevance
“…14 There is also experimental evidence that most carcinosarcomas are monoclonal neoplasms rather than representing collision tumours. 15,16 p53 expression is usually concordant between the epithelial and mesenchymal components exhibiting a diffuse, null or wild-type pattern of expression, thus suggesting a common lineage for the two components. 16 Occasionally, the sarcomatous component only manifests itself in the metastasis or recurrence of a high-grade endometrial carcinoma.…”
Section: Histogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…14 There is also experimental evidence that most carcinosarcomas are monoclonal neoplasms rather than representing collision tumours. 15,16 p53 expression is usually concordant between the epithelial and mesenchymal components exhibiting a diffuse, null or wild-type pattern of expression, thus suggesting a common lineage for the two components. 16 Occasionally, the sarcomatous component only manifests itself in the metastasis or recurrence of a high-grade endometrial carcinoma.…”
Section: Histogenesismentioning
confidence: 99%
“…Survival is largely dependent on stage, but overall 5-year survival is~35%, being worse than that of other 'high-grade' endometrial carcinomas. 15 There is some evidence that behaviour is worse when the epithelial component comprises non-endometrioid (serous, clear cell or undifferentiated) rather than endometrioid carcinoma. A relatively recent study has shown that in stage I uterine carcinosarcomas, the nature of the mesenchymal component is a powerful prognostic indicator; those tumours with heterologous elements having a significantly worse prognosis than those with only homologous mesenchymal component (3-year survival 45 vs 93% for heterologous and homologous neoplasms, respectively).…”
Section: Histogenesismentioning
confidence: 99%
“…IJBR (2015) 6 (09) www.ssjournals.com It is believed that uterine carcinosarcoma is similar to metaplastic endometrial carcinoma so generally management is based on treatment protocols for high-risk endometrial carcinoma [12] Most commonly followed treatment modality is TAH with BSO, pelvic lymphadenectomy, and para-aortic lymph-node sampling with peritoneal washings [1]. It has been seen that patients having predominant epithelial element show a better response rate to chemotherapy (87.5%) than with patients with predominat sarcomatous component [13].…”
Section: Discussionmentioning
confidence: 99%
“…Algumas neoplasias poderão ter origem Revista Científica da Ordem dos Médicos www.actamedicaportuguesa.com Luz R, et al Carcinossarcoma uterino, Acta Med Port 2016 Oct;29 (10): [621][622][623][624][625][626][627][628] biclonal e serem tumores de colisão. 3,4 O carcinossarcoma surge mais frequentemente em mulheres com idade avançada (entre os 60 e 70 anos) e de raça negra. Outros fatores de risco identificados são semelhantes aos do carcinoma do endométrio e incluem nuliparidade, obesidade, uso de estrogénios exógenos, uso de tamoxifeno e história de radioterapia pélvica.…”
unclassified